FORENSIC ASPECTS OF THE ACTIVITIES OF AN ANESTHESIOLOGIST- RESUSCITATOR - Hakimov Sarvar Abduazimovich (TADQIQOTLAR.UZ, 2024)
Citizens' access to qualified medical care is guaranteed by the state. Currently, special attention is paid to measures aimed at improving the quality of medical care. In this regard, a special place is occupied by commission forensic medical examinations  related to the activities of medical personnel. It should be noted that the analysis of these materials is neglected.